Home alone: Widows' Well-Being and Time - Maja Adena; Daniel Hamermesh; Michal Myck; Monika Oczkowska (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Using data from the Survey of Health, Ageing and Retirement in Europe (SHARE, 2004-17) and time diaries from Poland (2013), the U.S. (2006-16), the U.K. (2014-15) and France (2009-10), we examine differences between widowed and partnered older women in well-being and its development in widowhood. Most importantly, our analysis accounts for time use, an aspect which has not been studied previously. We trace the evolution of well-being of women who become widowed by comparing them with their matched non-widowed 'statistical twins' and examine the role of an exceptionally broad set of potential moderators of widowhood's impact on well-being. We confirm a dramatic decrease in mental health and life satisfaction after the loss of partner, followed by a slow partial recovery over a five-year period. An extensive set of controls recorded prior to widowhood, including detailed family ties and social networks, provides little help in explaining the deterioration in well-being. Unique data from time-diaries kept by older women in several European countries and the U.S. tell us why: the key factor behind widows' reduced well-being is increased time spent alone.
Keywords: I31; I19; J14; 330; widowhood; well-being; social networks; time use